Global Sports Fandom in South Korea American Major League Baseball and Its Fans in the Online Community - Cho, Younghan; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Palgrave Macmillan, 2020)
This book explores the transformation of cultural and national identity of global sports fans in South Korea, which has undergone extensive cultural and economic globalization since the 1990s. Through ethnographic research of Korean Major League Baseball fans and their online community, this book demonstrates how a postcolonial nation and its people are developing long-distance affiliation with American sports accompanied by nationalist sentiments and regional rivalry. Becoming an MLB fan in South Korea does not simply lead one to nurturing a cosmopolitan identity, but to reconstituting one$1 (Bs national imaginations. Younghan Cho suggests individuated nationalism as the changing nature of the national among the Korean MLB fandom in which the national is articulated by personal choices, consumer rights and free market principles. The analysis of the Korean MLB fandom illuminates the complicated and even contradictory procedures of decentering and fragmenting nationalism in South Korea, which have been balanced by recalling nationalism in combination with neoliberal governmentality.s
Introduction: The Cultural Politics of Sports in the Era of Globalization -- Part I: Sports Governmentality: Glocalization of American Sports in South Korea -- Sport and Crisis of Nation under Globalization -- Glocalization of Sports From Above: A Korean Baseball Player as a National Individual -- Glocalization of Sports From Below: Online Communities among Korean MLB Fans -- Part II: Undoing Nationalism: Ethnography of Korean Major League Baseball Fans -- The Making of the National Fandom and its Discontent -- The Emergence of Individuated Nationalism -- Articulation of the National, Regional and Global -- Postscript The (3z(BHere-and-Now(3y (Bof Global Sports Fandom.s
Keywords: Ethnology$1 (BAsia.s; Sports$1 (BSociological aspects.s; Sports sciences; Ethnography; Asia$1 (BPolitics and government.s; Asian Culture; Sociology of Sport and Leisure; Sport Science .; Ethnography; Asian Politics